From rural fields to urban kitchens: Structural change and the decline of women's work in India - Michael Peters; Pamela Torola; Lindsey Uniat; Fabrizio Zilibotti (Yale University, Economic Growth Center, 2024)
India's GDP per capita grew threefold between 1987 and 2019, coinciding with rapid urbanization. During this period, female labor force participation (FLFP) declined significantly. Consistent with this observation, we document a pronounced urban-rural participation gap, where FLFP is higher in poorer, rural labor markets. Using time-use data, we show that this is primarily driven by an extensive margin: in rural districts, women often engage in part-time activities, typically related to agriculture and informal family businesses. These activities are less common in urban areas, where some women take formal jobs, but a larger share withdraws from the labor market to focus on home production. We propose and estimate a model of household labor supply that aligns with these trends. The main drivers of the urban-rural participation gap are higher spousal incomes in cities, which reduce the marginal utility of female labor, and labor market distortions that depress women's urban wages below their marginal product. Counterfactual simulations show that economic growth is unlikely to provide a sharp reversal of this trend in future decades unless it is accompanied by changes in gender norms and labor market institutions.
Keywords: 330; Weibliche Arbeitskräfte; Arbeitsangebot; Strukturwandel; Städtischer Arbeitsmarkt; Ländlicher Arbeitsmarkt; Indien